2020
DOI: 10.3390/nu12041148
|View full text |Cite
|
Sign up to set email alerts
|

Natural Protein Tolerance and Metabolic Control in Patients with Hereditary Tyrosinaemia Type 1

Abstract: In a longitudinal retrospective study, we aimed to assess natural protein (NP) tolerance and metabolic control in a cohort of 20 Hereditary Tyrosinaemia type I (HTI) patients. Their median age was 12 years ([3.2–17.7 years], n = 11 female, n = 8 Caucasian, n = 8 Asian origin, n = 2 Arabic and n = 2 Indian). All were on nitisinone (NTBC) with a median dose of 0.7 g/kg/day (range 0.4–1.5 g/kg/day) and were prescribed a tyrosine (Tyr)/phenylalanine (Phe)-restricted diet supplemented with Tyr/Phe-free L-amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A nationwide study from Finland reported low median adult heigh z-scores in both transplanted and NTBC-treated subjects [ 31 ]. In contrast, a retrospective study from Birmingham showed an improvement in height z-scores from 8 years of age, reaching population standards by 16 years of age [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide study from Finland reported low median adult heigh z-scores in both transplanted and NTBC-treated subjects [ 31 ]. In contrast, a retrospective study from Birmingham showed an improvement in height z-scores from 8 years of age, reaching population standards by 16 years of age [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the main focus should be on increasing compliance to achieve improved metabolic control rather than further restricting food choices. Protein tolerance has been shown to increase with age which argues in favor of a simplified and relaxed diet especially in adolescents and adults [14].…”
Section: Discussionmentioning
confidence: 99%
“…This would also avoid significant age differences between relaxed and strict diet groups. Age can be a confounder in terms of protein tolerance [14] and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Data on phenylalanine supplementation was also collected. The dietary management in our centre has been previously described [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite considerable experience with dietary treatment in HTI, precise nutritional requirements are not well-defined. It has been reported that patients with HTI tolerate more natural protein with increasing age without compromising metabolic control [ 19 , 20 ]. In PKU, there is some evidence to suggest that maximizing natural protein intake may improve height growth and body composition parameters [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%